Strengthening Institutions Recipient of Compulsory Reporting Against the Prevalence of Drug Abusers in Lampung Province - Zainab Ompu Jainah; Erlina B.; Intan Nurina Seftiniara; Melisa Safitri; Hendri Dunan (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
The Recipient Institution of Compulsory Reporting opens the way for the government to eradicate drugs and cure the victims of drug abusers. Even so, socialization is felt to be lacking in society. People still view that victims of drug abuse are criminals and those who use drugs have a very big disgrace if they are known by their families and the surrounding community. The problems in this study are: How to strengthen the institution receiving the obligation to report on the prevalence of drug abusers in the province of Lampung? and What are the obstacles faced by recipient institutions that are required to report the prevalence of drug abusers? The research method used is a normative and empirical juridical approach. The results of the discussion in this study are the strengthening of reporting institutions on the prevalence of drug abusers in Lampung Province, including reporting drug abusers to mandatory reporting recipient institutions. After receiving mandatory reporting, a team of doctors consisting of doctors and psychologists conducts an assessment of narcotics abusers. The second process is the mechanism for implementing the rehabilitation through the Reporting Recipient Institution. Furthermore, addicts are tested urine (urinalysis) to detect the presence/absence of narcotics in the body of narcotics abusers. Provision of basic counseling is intended to increase patient motivation. The next stage is a re-evaluation which is intended to ensure that narcotics abusers are indeed using drugs or not. Narcotics addicts who have undergone mandatory reporting (shown by having an IPWL card) will not be legally processed. Constraints faced by recipient institutions are required to report on the prevalence of drug abusers in Lampung Province, including those related to regulatory policy constraints, socialization policies, coordination policies, human and institutional resources and management.